In silico Approaches to Identify Phthalic Acid Derivatives as Inhibitors Tyrosinase, α-Glucosidase, and Dipeptidyl peptidase-4: In silico Approaches to Identify Phthalic Acid Derivatives - Irianti, Tatang; Pangeran, Khrisna; Pratama, Binar; Purnomo, Hari; Ritmaleni (Iranian Journal of Pharmaceutical Sciences, 2025)
Integrating scientific and technological development in medicinal chemistry implies a great leap forward and speeds up the low-cost drug discovery process from natural resources. Therefore, in silico approaches were performed through molecular docking involving receptors crucial in metabolic processes, aiming to gain insights into how free radicals bind and how blood sugar levels can be lowered. The research aims to study the inhibitory mechanisms of phthalic acid derivatives such as tyrosine enzymes, alpha-glucosidase, and dipeptidyl peptidase-4 with in silico predictions. The in silico prediction instrument is in the form of computing software. Additional ligand sources were gained from a database of tyrosinase enzyme receptor (6JU9), alpha-glucosidase receptor (2JKE), and dipeptidyl peptidase-4 (1N1M). The active ingredients of Kenikir and Yacon leaves are used as test compounds with comparison drugs such as acarbose. The Diisooctyl Phthalate compound has an antioxidant potential through the 6JU9 target protein, with the most stable docking score of -81, 07. The target proteins for reducing blood sugar levels each have a value of -61.606 (2JKE ligand) and -86.945 (1N1M ligand). It is concluded that natural resources (Cosmos caudatus and Smallanthus sonchifolius) showed potential as natural drugs with an in silico approach study.